Aplikasi Bioherbisida Pra Tumbuh Ganda Rusa (Asystasia intrusa) untuk Pengendalian Gulma di Areal Perkebunan Kelapa Sawit - Vira Irma Sari; Alfin Suhendra (Politeknik Kelapa Sawit Citra Widya Edukasi, 2021)
The use of pre-emergence bioherbicide for controlling weeds could be alternatife because it more safe for environment and the process is easy to do. Bioherbicides could be made from weed waste around oil palm plantation, one of them is Ganda Rusa or Asystasia intrusa. These weeds contain allelochemical compounds that can inhibit various growth reactions in weeds and are dominance weeds in oil palm plantations. The objectives of this experiment were to obtain the alternative material for pre-emergence bioherbicide and to know the effectivity of pre-emergence Asystasia intrusa to weed’s growth and soil physical condition, and identify the dominant weed species that grow. This research conducted at research area in Desa Penarik, Kabupaten Muko-Muko, Bengkulu, from Januari until Februari 2021. This research was arranged in a factorial random block design with three replications and four treatments. The treatments are P0 (Control), P1 (Herbisida 1%), P2 (Bioherbicide 1 liter), P3 (Bioherbicide 2 liter). Each of treatments repeated three times. The data was analysis of variance at 5%, then it continued by Least Significance Different Test (LSD Test). The result showed that Asystasia intrusa could be as alternative material for pre-emergence bioherbicide and significantly affected to weed’s growth in 4 until 7 dayas after application. Bioherbicide 2 liter has potential to control weeds in oil palm plantation and not showed significantly difference to physics condition of Ultisol. The weed dominance it showed in area is Borreria alata.